SWI/SNF-Related SMARCA2 Gene Mutation Associated with Nicolaides–Baraitser's Syndrome: Follow-up Study - Akella, Radharamadevi (Journal of Pediatric Genetics, 2022)
Nicolaides–Baraitser's syndrome is a rare, dominantly inherited well-delineated syndrome caused by mutations in the SMARCA2 gene which is located on the small arm of chromosome 9. In this study, a de novo missense variant, which was identified in a 3-year-old boy by whole exome sequencing is reported. The de novo heterozygous V1198M missense variant in SMARCA2 gene in exon 25 is novel. Identifying the condition is crucial for the long-term management and family counseling. Follow-up over 4 years revealed improvements in overall performance.
Keywords: Nicolaides–Baraitser's syndrome; SMARCA2 gene; SWI/SNF; chromatin